Tandem Hydrogenolysis–Hydrogenation of Lignin‐Derived Oxygenates over Integrated Dual Catalysts with Optimized Interoperations. Issue 23 (18th November 2019) - Fang, Huihuang; Chen, Weikun; Li, Shuang; Li, Xuehui; Duan, Xinping; Ye, Linmin; Yuan, Youzhu
Abstract: The efficient hydrodeoxygenation (HDO) of lignin‐derived oxygenates is essential but challenging owing to the inherent complexity of feedstock and the lack of effective catalytic approaches. A catalytic strategy has been developed that separates C−O hydrogenolysis and aromatic hydrogenation on different active catalysts with interoperation that can achieve high oxygen removal in lignin‐derived oxygenates. The flexible use of tungsten carbide for C−O bond cleavage and a nickel catalyst with controlled particle size for arene hydrogenation enables the tunable production of cyclohexane and cyclohexanol with almost full conversion of guaiacol. Such integration of dual catalysts in close proximity enables superior HDO of bio‐oils into liquid alkanes with high mass and carbon yields of 27.9 and 45.0 wt %, respectively. This finding provides a new effective strategy for practical applications. Abstract : Dual cooperation : Hydrodeoxygenation of lignin‐derived oxygenates and bio‐oil can be effectively achieved by tandem hydrogenolysis–hydrogenation, whereby tungsten carbide effects C−O bond hydrogenolysis and Ni is mainly responsible for arene hydrogenation. Product distribution can be tuned by flexible integration of the active catalysts. A total mass and carbon yield of 27.9 and 45.0 wt %, respectively, are obtained by conversion of the bio‐oil.